Reservoir ecological operation on sediment-laden river considering wetland protection - Yang, Yichen; Liu, Bojun (Frontiers in Environmental Science, 2023)
Reservoir ecological operation has become an important means of ecological protection and restoration. The operation of reservoirs on sediment-laden rivers with water supply, sediment transport, flood control, wetland protection, and power generation as the primary objectives is a challenge in water resources management. Currently, most studies on reservoir ecological operation models involve a single ecological objective, and the inadequacy of the corresponding ecological constraint conditions makes it difficult to optimize reservoir ecological operation. To address these challenges, this study considers comprehensive water shortage, ecological water shortage, effective sediment transport in the river, and reservoir power generation as objective functions to establish an ecological operation model of sediment-laden river reservoirs for wetland protection. In this model, the ecological flow at key sections and water quantity discharged into the ocean are added as the constraint conditions to generate optimal operation schemes that reflect ecological benefits. The case study of the Xiaolangdi Reservoir (XLDR) on the Yellow River, China shows that with this model, the multi-objective requirements of water supply, ecology, sediment transport, flood control, and power generation in the XLDR could be met synergistically by optimizing the average daily discharge of the reservoir. Although the generated ecological operation schemes consider the demand for wetland protection, the reservoir flood control, sediment transport and power generation were not affected, and the latter two even showed improvement. In addition, this model has stronger applicability for large reservoirs. In dry years, small and medium reservoirs require water transfer, water-saving, and other measures required to alleviate possible water shortage.